If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5(y + -2) = 8 Reorder the terms: 5(-2 + y) = 8 (-2 * 5 + y * 5) = 8 (-10 + 5y) = 8 Solving -10 + 5y = 8 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '10' to each side of the equation. -10 + 10 + 5y = 8 + 10 Combine like terms: -10 + 10 = 0 0 + 5y = 8 + 10 5y = 8 + 10 Combine like terms: 8 + 10 = 18 5y = 18 Divide each side by '5'. y = 3.6 Simplifying y = 3.6
| 2+4w=26 | | 3x-15=x+15 | | 3y-6=-27 | | 3x-7=(x+4) | | 4x-4=-2 | | 7x-3=-5+6x-(4x+3) | | x^3-2=0 | | 10-8x=27-15x | | -x+11=5x+12-(7x-2) | | S^2-2s-8=0 | | 6x^2+4=10 | | 81-2(x-1)2=51 | | 3x^2-4=4-3x^2 | | -12x-9x=9x+24 | | 2x+5-15+3x=5 | | 6x(5x+3)=18x | | 5k-12=20 | | 2x+4(2x+4)=50 | | 8x-8=3x+4 | | 6x+80=9x-7 | | 12-7x=162-42x | | 129-9x=9x+15 | | 2*x*x+5=10 | | 9+.44444444444=19 | | 6x+83=9x-7 | | 2x^3-x^2-1=0 | | 2+45-3/2=12b | | 8t-5=19 | | 6x-11-7x+12= | | 4x^2-4x+4=0 | | -x^2+x-12=0 | | 4(y+3)=7-5y |